The study of water bug fauna (Insecta: Hemiptera) in My Son Sanctuary, Quang Nam Province - Thi Dao, Chu; Thi Anh Nguyet, Nguyen; Anh Duc, Tran (VNU Journal of Science: Natural Sciences and Technology, 2017)
My Son was listed as a UNESCO World Cultural Heritage Site in 1999. However, My Son is now negatively affected by on-going human activities. One of the solutions to conserve the My Son sanctuary is based on the ecosystem approach. The ecosystem approach is based on the application of appropriate scientific methodologies focused on levels of biological organization, providing a scientific basis for developing solution to the ecosystem structure. The results of presented in this paper, focusing on the fauna of water bugs (Insecta: Hemiptera), is a part of the study to investigate the species composition in the area, in order to compile a baseline data for proposing and developing a model for applying ecological and irrigation solutions in My Son sanctuary, Quang Nam province. Field surveys conducted along Khe The stream, in the area of My Son sanctuary in August 2016 and April 2017 have yielded a total of 36 water bug species, belonging to 29 genera, 13 families of two infraorders Gerromorpha and Nepomorpha. Among 13 families found in the studied area, the family Gerridae has the highest number of species, 14 species belonging to nine genera, followed by the family Veliidae with four species. Nepidae and Naucoridae have three species each. The remaining families contain only one or two species each. This study has provided the first inventory on water bug fauna of the area of the My Son sanctuary.